Extraterritorial application of human rights treaties law, principles and policy - Milanovic, Marko (Oxford : Oxford University Press, 2011)
This title makes sense of the often confusing case law on this issue and proposes a new way of interpreting extraterritorial human rights obligations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights; Treaties; International relations